Numerical predictions of progressive collapse in reinforced concrete beam-column sub-assemblages: A focus on 3D multiscale modeling - Long, Xu; Iyela, Percy M.; Su, Yutai; Atlaw, Meklit M.; Kang, Shao-Bo (Engineering structures, 2024)
The progressive collapse of reinforced concrete (RC) beam-column sub-assemblage under catenary action (CA) using the alternate load path method to evaluate structures' robustness has raised much attention in the past decade, both in experimental tests and finite element (FE) simulations. However, a comprehensive multiscale method within concrete to assess structural robustness against progressive collapse, explicitly surrounding concrete matrix under CA, is generally lacking and has not been thoroughly explored in the relevant literature. This study aims to develop an FE macromodel to reliably simulate the progressive collapse resistance of seismic and non-seismic RC beam-column sub-assemblages. The proposed macroscale FE models are extensively validated by experimental results dominated by the CA and excessive deformation of RC beam-column sub-assemblages. Then, the macroscale FE model is further partitioned at the critical region with high-stress concentration to establish a sub-model and elucidate the underlying mesoscopic mechanism to motivate the CA by performing sub-modeling analysis. A 150 mm × 150 mm × 150 mm mesoscale heterogeneous model is established to be composed of aggregates, interfacial transition zone (ITZ), pores, and mortar by 3D voxel and Voronoi-based methods. The numerical predictions of the three macroscale models demonstrate good agreement of the overall deformation and load resistance trends with experimental results at both structural and sectional levels, but an overestimation of the load resistance peak is observed when concrete is crushed. Compared to the macroscale models, the sub-modeling analysis provides a more in-depth understanding of localized phenomena such as cracks and fractures. The 3D mesoscale model is further investigated with different aggregate volume fractions following the Fuller gradation. It is found that aggregates and ITZ (higher porosity, lower elastic modulus, and lower tensile strength compared to the bulk mortar) are more prone to concrete failure mechanisms without considering the role of reinforcement leading to the CA at the mesoscale, maintaining the concrete properties of the three macroscale models. In terms of the material constitutive model, the concrete damage plasticity model, and cohesive elements for mortar and ITZ, respectively, under uniaxial compression and tension behavior, the importance of interface bonding in CA of the surrounding concrete matrix is underlined. Additionally, the established mesoscale modeling method facilitates comprehension of the responses exhibited by macroscale RC sub-assemblies, ultimately shedding light on fracture initiation and propagation mechanisms. •Numerically predict a macroscopic model resistance under catenary action.•Further improve accuracy and dependability of resistance capacity in submodelling.•Unveil the resistance contributions in mesoscale modeling under progressive collapse.